The Relationship between Mothers' Parenting Stress and Spiritual Well-Being and the Behavioral Disorders of Children with Specific Learning Disorders: Mediated by the Quality of Married Life - Zarghami, Soheila; Bakhtiarpour, Saeed; Heidari, Alireza (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Raising children with specific learning disorders (SLDs) is a stressful experience, and one type of stress experienced by the mothers of these children is parenting stress. The present study aimed to investigate the relationship between mothers' parenting stress and spiritual well-being and the behavioral disorders of children with SLDs through the mediating role of quality of married life. Methods: The statistical population of this descriptive-correlational study consisted of all the mothers of children with specific learning disorders (SLDs) in Shiraz (Iran) in 2022. A sample of 218 boys with SLDs and their mothers was conveniently selected. The Parenting Stress Index, the Spiritual Well-Being Scale, the Revised Dyadic Adjustment Scale, and the Child Behavior Checklist were used for data collection. The proposed model was evaluated using structural equation modeling (SEM) in SPSS and AMOS. Results: All the direct paths, except for the path of parenting stress to children's behavioral disorders, were significant (P<0.001). The indirect paths from parenting stress to children's behavioral disorders, mediated by the quality of married life, and the path from spiritual well-being to children's behavioral disorders, mediated by the quality of married life, were also significant (P<0.001). Conclusions: Based on the results, the adjusted final model had an optimal fit and constitutes a major step towards identifying the factors affecting the behavioral disorders of children with SLDs.